Moroccan Women in the Domestic Services Sector: Recognizing The Unrecognized: Fez as a Case Study - Karima Mechouat (European Scientific Journal, ESJ, 2017)
The present paper aims to uncover the socio-economic and legal situation of women involved within the domestic services sector. It draws on parts of the findings brought about by a research paper I conducted in the fulfillment of the requirements for the degree of doctorate at the Faculty of Letters and Human Sciences in Fez, Morocco. Being more essentially based on ethnography, the study was carried out through the use of observation, focus group and structured/semi-structured interviews which were conducted and analyzed in the light of the established theoretical framework of this exploratory investigation. What is new in this article is the fact that the investigation’s findings will be analysed and discussed through a critical rereading of the Moroccan Labour Law on domestic workers to gauge the extent to which it complies with the International Labour Standards set by the Domestic Workers Convention. As a result of structural adjustment, a considerable number of unemployed workers are urged to invade the informal sector. This study reveals that women involved in the domestic services sector as an informal and feminized sector are not only economically and socially marginalized, but they are also marginalized at the legislative level. All this indicates the importance of recognizing the unremunerated and the under-remunerated contributions of women to the domestic services sector and to all aspects of development. It also suggests the urgent need to amend the labour law on domestic workers and bring it in line with the International Labour Organization Standards to improve domestic workers’ conditions.